Retracted: A new class of copper(I) complexes with imine‐containing chelators which show potent anticancer activity. (30th January 2020) - Choodari Milani, Neda; Maghsoud, Yazdan; Hosseini, Mahdieh; Babaei, Abouzar; Rahmani, Hamidreza; Roe, Stephen Mark; Gholivand, Khodayar
Abstract : Seven novel complexes (C1 –C7 ) were synthesized by the interaction between Cu(I) metal cation, L1, L2, L3, X and PPh3, where L1 –L3 are derivatives of ((pyridine‐2‐ylmethylene)amino)phenol imine ligands and X = Cl −, Br −, I −, NCS − . All the complexes were characterized using infrared, 1 H NMR and 31 P NMR spectroscopies. The crystal structures of C1 –C7 were also determined using single‐crystal X‐ray diffraction. The organization of the crystal structures and the intermolecular interactions are discussed. The supramolecular assemblies are driven by cooperative π…π interactions and hydrogen bonds, followed by CH…π linkages. The potential anticancer effect of C1 –C7 was assessed for human glioblastoma cells using several anticancer experiments, which showed that these complexes have marked anticancer property against U87 cells. It was also found that the minimum and maximum anticancer effects are shown by C3 ‐ and C4 ‐treated samples, respectively. Furthermore, theoretical approaches were used to investigate the nature of metal–ligand interactions which suggest a closed‐shell and electrostatic character for Cu…N, Cu…P and Cu…X bonds. Abstract : Seven novel Cu(I) complexes with imine‐containing chelators are synthesized. The complexes are useful anticancer agents in the biological treatment of U87 glioblastoma cell line.